Localization of the kdsA gene with the aid of the physical map of the Escherichia coli chromosome. - Woisetschläger, M (1988)
The isolation and analysis of two recombinant plasmids containing the kdsA gene from Escherichia coli chromosomal gene libraries is reported. The subfragments obtained from the inserts correspond to the fragment pattern around coordinate 1,282 kilobases of the physical map of the E. coli chromosome (Kohara et al. Cell 50:495-508, 1987). The kdsA gene has been located at coordinates 1,282 through 1,283 kilobases, corresponding to min 26.7 in the classical map coordinates. The kdsA gene is transcribed from this position toward the nearby nar gene.